INFORMATION SYSTEM CONTROL PURCHASE ORDER (PO) BAHAN BAKAR MINYAK PADA PT. ALIRAN KARYA MENGGUNAKAN VISUAL BASIC 6.0 - Mesterjon, Mesterjon; Hermawansyah, Hermawansyah; sono, Aji Sudar (UNIVED Press, 2013)
PT . Aliran Karya is working partner PT . Pertamina acts as a provider of transportation facilities in the form of Industrial Fuel tank cars at once as Agent BBM Solar Industry PT . Pertamina Patra Niaga. Serving reports information on PT Aliran Karya This is still using manual system that is using Microsoft Word and Microsoft Excel . As jobs become ineffective and inefficient . That requires an information system that is capable of displaying the information to be more efficient. The purpose of this study was to make Control Information System Purchase Order ( PO ) Fuel ( BBM) Solar Industry at PT . Aliran Karya Using Visual Basic 6.0 to information presentation can be more efficient . Information systems can be an alternative to the PT . Work flow to make more efficient information presentation , more attractive and easier to use , and able to pass up the printing of reports available in the Information Systems Control Purchase Order